2020
DOI: 10.1002/ijgo.13366
|View full text |Cite
|
Sign up to set email alerts
|

Fertility intentions among couples in Shanghai under COVID‐19: A cross‐sectional study

Abstract: Objective: To evaluate fertility intensions among couples in Shanghai under the novel coronavirus infection (COVID-19) pandemic against the backdrop of persistently low fertility. Methods: A cross-sectional study was carried out using data from studies conducted before the COVID-19 pandemic. Data were collected regarding sociodemographic characteristics, history of reproduction and gynecology, fertility intention before and after the COVID-19 pandemic, female psychological state, and the impact of the COVID-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 20 publications
2
59
1
Order By: Relevance
“…2 Since then, surveys conducted in Europe, in Shanghai, and by the Guttmacher Institute in the US have reported that, in high-income countries, people's pregnancy intentions have shifted, with 30% to 80% of those who reported an intention to become pregnant within the next year before the COVID-19 outbreak postponing or abandoning their plans. [3][4][5][6] Recent data suggest that, although the number of births was already decreasing in the US, the decrease between December 2019 and December 2020 was 26% greater than the average year-over-year decrease across the prior 4 months. 7 COVID-19-related changes in pregnancy intentions have the potential to accelerate the steady decrease in fertility rates seen since the mid-1900s in almost all regions of the world.…”
Section: Introductionmentioning
confidence: 99%
“…2 Since then, surveys conducted in Europe, in Shanghai, and by the Guttmacher Institute in the US have reported that, in high-income countries, people's pregnancy intentions have shifted, with 30% to 80% of those who reported an intention to become pregnant within the next year before the COVID-19 outbreak postponing or abandoning their plans. [3][4][5][6] Recent data suggest that, although the number of births was already decreasing in the US, the decrease between December 2019 and December 2020 was 26% greater than the average year-over-year decrease across the prior 4 months. 7 COVID-19-related changes in pregnancy intentions have the potential to accelerate the steady decrease in fertility rates seen since the mid-1900s in almost all regions of the world.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that Polish people had been worried about the COVID-19 pandemic and that fear of the virus spreading is a significant predictor of emotional distress [10,11]. Our study shows that, concerns related to the pandemic are also having an overall impact on Polish people's reproductive plans.…”
Section: Discussionmentioning
confidence: 52%
“…Even though, the survey from Italy revealed similar observations [12], this may not be a global trend. The study that was performed to evaluate reproductive intentions among couples in Shanghai under the COVID-19 pandemic, revealed that the decrease in income did not significantly affect the reproductive intention [11]. Interestingly, the pandemic has had a positive impact on emotional relationships between partners due to the overall increase in emotional intimacy, sensitivity and mutual support.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Yassa et al reported an increase in anxiety and concern about pregnancy and childbearing during the COVID-19 pandemic [29]. Nonetheless, in the study by Zhu et al, childbearing desire had not changed compared to before the COVID-19 pandemic in 66.2% of the participants and none of the couples had any anxiety about this pandemic [30]. Consequently, the present study used the TPB as a model for path analysis to investigate the role of the COVID-19 pandemic in the childbearing intentions of Iranian couples using anxiety about COVID-19 as the mediating variable.…”
Section: Introductionmentioning
confidence: 92%